A study on families, elite and politics: the trajectory of the viscount of Congonhas do Campo, and the Monteiro de Barros (Ágora Journal, 2024)
This work aims to highlight the importance of the Monteiro de Barros family for the consolidation of the Brazilian national state in the nineteenth century. In addition, we highlight the political trajectory of a specific character, Lucas Antônio Monteiro de Barros, the viscount of Congonhas do Campo. Inserted in a context of domination of elite families, the Monteiro de Barros fit into the moulds, such as marriages, academic training and political occupation and in the state bureaucracy. Therefore, we bring the main research on elites in Brazil in the context of the eighteenth and nineteenth centuries, in an attempt to locate them in a larger set. Our work will be about the bibliographic discussion, however, some sources will be evoked when necessary for support, mainly of a biographical nature. In addition, it is an initial investigation into the private and public life of the Viscount of Congonhas do Campo.
Keywords: Monteiro de Barros; family; elite; Minas Gerais